Historical and legal overview of the State and Advocacy interaction within the system of human rights and freedoms protection - S. S. Bandurka (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the interaction between the State and the Advocacy as a human rights protection organisation from the historical and legal perspective. At all times of its formation and development, the Advocacy has operated within a certain system of state and social relations and was called upon to promote the protection of human interests in accordance with the laws of the State in which it operated. The activities of the Advocacy have always been multifaceted, and therefore the article describes various methods of studying the interaction between the State and the Advocacy from the historical and legal perspective. The necessity of studying the interaction between the State and the Advocacy to refer to the legal documents of the past which regulated the activities of the Advocacy and its relationship with the State is emphasised.